Stable silencing of IGF1R using Lentiviral-mediated shRNA in HEK293T cells - Nasehi, L.; Ghahremani, M. H.; Yavari, K.; Hadjati, J.; Fallah, A.; Abdolhossein Zadeh, B.; Saltanatpour, Z. (Cellular and Molecular Biology, 2017)
Insulin-like growth factors are among the peptide mitogens that regulate cell proliferation and differentiation as well as mediator of antiapoptotic signals. The imbalance between the expression and activities of these molecules may lead to malignancy in cells. Evidences have suggested the insulin-like growth factor 1 receptor (IGF-1R) signaling pathway as a therapeutic target in the management and treatment of cancer. In this present study, we have generated silencing stable clones of HEK cells using six different pGIPZ (lentiviral vector) shRNAs targeted to human IGF-1R gene and a pGIPZ non-silencing shRNAmir lentiviral vector (as negative control). The recombinant lentiviral vectors were separately transduced into human embryonic kidney 293 T (HEK293T) cell lines. The knockdown of IGF-1R was confirmed by reverse transcription polymerase chain reaction (RT-PCR) and the relative IGF-1R mRNA levels were expressed as a ratio of IGF-1R to Î²-actin by REST software. The results showed significant reduction in the expression of IGF-1R mRNAs in cells transduced with all six pGIPZ-IGF-1R recombinant lentivirals compared to non-silencing negative control. No significant difference was observed among the six cassettes. Results indicated that recombinant lentiviral vectors provided an efficient and stable knockdown of IGF-1R providing useful tool for IGF-1R pathway studies.